Dzielimy się doświadczeniemMinimally invasive right Anterolateral Thoracotomy for Repair of Congenital Heart Defects - Pawlak, Szymon; Ciurysek, Magdalena; Skalski, Janusz H.; Wites, Marek; Radziszewska, Ewa; Gburek, Tadeusz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2008)
Background: A major goal behind development of novel cardiac surgical techniques is further reduction of post-operative complications and improvement of quality of life after surgical treatment of congenital heart disease. Material and Methods: Our study retrospectively analyses results of a series of 18 patients in whom the atrial septal defect was closed through a right anterolateral thoracotomy approach. Findings were compared to the same number of patients operated on through the standard approach. Data assessed were: time of operation, appearance of complications, postoperative loss of blood and duration of rehabilitation. Results: The mean time of operation performed through a right thoracotomy was approximately 33% longer than the time of a standard operation. However, the postoperative drainage was approximately 42% lower. Rehabilitation time was 18 days shorter. Conclusions: Right anterolateral thoracotomy incision is a safe alternative to median sternotomy in atrial septal defect repair in young patients. This approach however is more difficult to perform and it should be reserved for more experienced surgeons. It is important that no pulmonary valve repair or close PDA is possible through a right anterolateral approach.